70th anniversary of the birth of Academician Edmundas Kazimieras Zavadskas - Šaparauskas, Jonas; Turskis, Zenonas; Merkuryeva, Galina V.; Liias, Roode (Technological and Economic Development of Economy, 2014)
"70th anniversary of the birth of Academician Edmundas Kazimieras Zavadskas review."Technological and Economic Development of Economy, 20(2), pp. 182-192